How can monetary policy affect the economic activity - Borda, Patrice ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Seeks to measure the persistence of shocks on the output within the framework of multi-basesd sector model. Analyzes the consequence of sectoral and aggregate shocks on the GDP through a restricted VAR and Bayesian VAR.